PRODUCTION OF Ge1-xLnxS MONOCRYSTALS AND THEIR ELECTROPHYSICAL AND PHOTOELETRIC PROPERTIES - Alekperov, Aydin (JOURNAL OF ADVANCES IN PHYSICS, 2015)
Among semiconductor materials wich can be citilized for recording optical information and holograms of considerable interest are layered materials.Inparticulas, GeSmonocrystals belong to them. A unique device of germanium sulphide that can contain a great quantity of lithium ionehaz been created recently of the University North Carolina. Such material is perfectly suitable as starting stock in manufacturing solar panels. Along with these properties germaniummonosulphideposseffes change-over and memory effects. To widen the scope of using GeSmonocrystal it was introduced into the matrix of atoms of rare-earth elements (Nd,Sm,Gd). The present research explores the formation of Ge1-xLnxS (where Ln-Nd.Sm,Gd) monocrystals and studies their electrophysical and photoelectrical properties.